Water management in the Argentine semiarid Chaco: a historical perspective on social-ecological systems - Arístide, Pablo (2016)
This article explores how historical processes related to water management, land use and bio-geophysical conditions, would have structured the current socio-ecological situation at the Figueroa Irrigation System (Santiago del Estero, Argentina). The study focuses on a peasant community through an oral history approach. In addition, historic technical reports about irrigation systems and river dynamics, and other secondary information were reviewed and compared with local peasant testimonies. The results suggest that government actions?taken at regional level on the Salado River basin?had a negative impact on the local agro-ecosystem and on management that had been adapted to local ecosystem dynamics. This study proposes that past events still influence river dynamics and therefore land use and natural resources management of local peasants. The role of local historical perspectives is a key element to understand social-ecological system changes and to forecast future trajectories.